Risk factors associated with the progression from keloids to severe keloids. Issue 7 (5th April 2022) - Liu, Ruolin; Xiao, Haitao; Wang, Ru; Li, Wei; Deng, Ke; Cen, Ying; Xu, Xuewen
Abstract: Background: Keloids are benign fibrous growths that are caused by excessive tissue build-up. Severe keloids exert more significant effects on patients' quality of life than do mild keloids. We aimed to identify factors associated with the progression from mild keloids to severe keloids, as distinct from those associated with the formation of keloids. Methods: In this retrospective case-control study, 251 patients diagnosed with keloids at West China Hospital between November 2018 and April 2021 were grouped according to the severity of lesions (mild [ n  = 162] or severe [ n  = 89]). We collected their basic characteristics, living habits, incomes, comorbidities, and keloid characteristics from Electronic Medical Records in the hospital and the patients' interviews. Conditional multivariable regression was performed to identify the independent risk factors for the progression of keloids. Results: Eighty-nine patients (35.5%) were classified as having severe keloids. We found the distribution of severe keloids varied with sex, age, excessive scrubbing of keloids, family income, the comorbidity of rheumatism, disease duration, characteristics of the location, location in sites of high-stretch tension, the severity and frequency of pain, the severity of pruritus, and infection. Multivariable analysis revealed significant associations between severe keloids and infection (odds ratio [OR], 3.55; P  = 0.005), excessive scrubbing of keloids (OR, 8.65; P  = 0.001), low or middle family income (OR, 13.44; P  = 0.021), comorbidity of rheumatism (OR, 18.97; P  = 0.021), multiple keloids located at multiple sites (OR, 3.18; P  = 0.033), and disease duration > 15 years (OR, 2.98; P  = 0.046). Conclusion: Doctors should implement more active and thorough measures to minimize the progression of mild keloids in patients who have any of the following risk factors: infection, excessive scrubbing of keloids, low or middle family income, comorbidity of rheumatism, multiple keloids located at multiple sites, and disease duration > 15 years.